Fructooligosaccharides and β-fructofuranosidase production by Aspergillus japonicus immobilized on lignocellulosic materials - Mussatto, Solange I. (2009)
This work describes the fructooligosaccharides (FOS) and β-fructofuranosidase (FFase) production from sucrose (200 g/l) by Aspergillus japonicus ATCC 20236 immobilized on different lignocellulosic materials including brewer's spent grain, wheat straw, corn cobs, coffee husks, cork oak, and loofa sponge. Transfructosylating (Ut) and hydrolyzing (Uh) activities of FFase were also determined. The FOS production and FFase activity ranged from 128.35 to 138.73 g/l, and 26.83 to 44.81 U/ml, respectively, for cells immobilized in the different carriers. Corn cobs was the best support material since gave the highest results of microorganism immobilization (1.49 g/g carrier), FOS and FFase production, with FOS productivity (6.61 g/l h) and yield (0.66 g/g based on total substrate; 0.73 g/g based on consumed substrate) higher than those obtained by free cells system. Moreover, the ratio Ut/Uh of FFase, parameter of importance for elevated FOS production, was greater for cells immobilized in corn cobs than for free cells. Such results demonstrated that corn cobs can be successfully used as carrier for immobilization of the fungus A. japonicus, for the production of FOS and FFase.